Banjarese: Self-Concept, Identity and River Culture - Abdurrahman, Abdurrahman; Abduh, Muhammad (The Pontianak State Institute of Islamic Studies, 2019)
Self-concept is the core of individual personality, which plays a role in determining and directing individual behavior. Self-concept cannot be separated from virtuous values that arise from self-identity. This article discusses the philosophy of life and the cultural values of the Banjar people